What Have We Learnt About the Treatment of Juvenile-Onset Systemic Lupus Erythematous Since Development of the SHARE Recommendations 2012? - Gallagher, Kathy L.; Patel, Pallavi; Beresford, Michael W.; Smith, Eve Mary Dorothy (Frontiers in Pediatrics, 2022)
Introduction Juvenile-onset systemic lupus erythematous (JSLE) is a rare multisystem autoimmune disorder. In 2012, the Single Hub and Access point for paediatric Rheumatology in Europe (SHARE) initiative developed recommendations for the diagnosis/management of JSLE, lupus nephritis (LN) and childhood-onset anti-phospholipid syndrome (APS). These recommendations were based upon available evidence informing international expert consensus meetings. Objective To review new evidence published since 2012 relating to the management of JSLE, LN and APS in children, since the original literature searches informing the SHARE recommendations were performed. Method MEDLINE, EMBASE and CINAHL were systematically searched for relevant literature (2012-2021) using the following criteria: (1) English language studies; (2) original research studies regarding management of JSLE, LN, APS in children; (3) adult studies with 3 or more patients <18-years old, or where the lower limit of age range ≤16-years and the mean/median age is ≤30-years; 4) randomised controlled trials (RCTs), cohort studies, case control studies, observational studies, case-series with >3 patients. Three reviewers independently screened all titles/abstracts against predefined inclusion/exclusion criteria. All relevant manuscripts were reviewed independently by at least two reviewers. Data extraction, assessment of the level of evidence/methodological quality of the manuscripts was undertaken in-line with the original SHARE processes. Specific PUBMED literature searches were also performed to identify new evidence relating to each existing SHARE treatment recommendation. Results Six publications met the inclusion/exclusion criteria for JSLE: three RCTs, one feasibility trial, one case series. For LN, sixteen publications met the inclusion/exclusion criteria: eight randomised trials, three open label prospective clinical trials, five observational/cohort studies. For APS, no publications met the inclusion criteria. The study with the highest evidence was an RCT comparing belimumab versus placebo, including 93 JSLE patients. Whilst the primary-endpoint was not met, a significantly higher proportion of belimumab-treated patients met the PRINTO/ACR cSLE response to therapy criteria. New evidence specifically addressing each SHARE recommendation remains limited. Conclusion Since the original SHARE literature searches, undertaken >10-years ago, the main advance in JSLE treatment evidence relates to belimumab. Additional studies are urgently needed to test new/existing agents, and assess their long-term safety profile in JSLE, to facilitate evidence-based practice.